Impact of School Teachers Inclusive Teaching Practices on the Learning Outcomes of Children with Special Needs: Lecture note approach (International Journal of Scientific Research in Science and Technology, 2025)
Inclusive education plays an important role in today school system. Teachers support children with special needs in regular classrooms. This paper studies the impact of inclusive teaching practices on learning outcomes of children with special needs. Teachers use strategies like differentiated instruction peer learning and supportive classroom environment. These practices help improve academic performance social skills and confidence of CWSN. The study shows that effective inclusive practices lead to positive learning outcomes.